History of Salt in Antiquity and its Historiographical Trajectory - Morère Molinero, Nuria Elisa; Domínguez del Triunfo, Helena (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
The aim of this paper is to analyze the historiographic development of a recent area of study: the history of salt, with a primary focus on Antiquity. The scope is to analyze how and within which lines of historical thought the history of salt was conceived, its development and focuses, and how it has consolidated and been integrated into current historiographic trends and practices. In fact, salt has been implicated in the first historical studies due to its economic relevance and state intervention, both of which have provided the primary historical sources of Antiquity. The springboard for these initial studies – which were based on early studies of nascent archeology – were the thematic histories and the global history concerning the individuals in society that were created by the Ecole des Annales, especially third-generation members like Jacques Le Goff. This consolidation of the historical studies of salt developed with a focus on other periods of history that would soon extend to Antiquity. Local archeological studies in large saltproducing regions will mark its identification and consolidation as a field of study, together with the nature of salt in connection with other areas such as diet, foodstuff conservation, and cultural technology. At present, the history of salt in Antiquity is fully defined and participates in the new trends of historical research and archeology. The written sources are being analyzed from different perspectives in combination with other areas of research, and at the same time large interdisciplinary teams are being created, as well as projects of great relevance and fieldwork that combines a focus on localized regions with those of greater expanse, and that concentrate on different periods of history in their continuity. Methods adopted from other disciplines whose focus is on the environment and territory are also being used. All this presages the development of intensive fieldwork for the upcoming years in relation to areas of salt production, and related technology as well as the framework of its exploitation.